Pengembangan Website Lembar Kerja Siswa Berbasis Penemuan Terbimbing Pada Materi Bangun Ruang Sisi Datar - Kamilia, Defi; Baidowi, Baidowi; Hapipi, Hapipi (FKIP Universitas Mataram, 2021)
The purpose of this research was to develop a studentÃƒÂ¢Ã¢Â‚Â¬Ã¢Â„Â¢s worksheets website based on guided discovery on polyhedron concept of 8th grade at MTsN. StudentÃƒÂ¢Ã¢Â‚Â¬Ã¢Â„Â¢s worksheets website based on guided discovery was studentÃƒÂ¢Ã¢Â‚Â¬Ã¢Â„Â¢s worksheets which arranged based on the phases of the guided discovery model, and presented in a website. This website created for local network. The purpose of developing this product was to resolve the weaknesses of printed studentÃƒÂ¢Ã¢Â‚Â¬Ã¢Â„Â¢s worksheets and also the weaknesses of applying guided discovery models. The research methodology used in developing the product was 4D (Define, Design, Development, Dissemination). The technique of collecting data was using interview and questionnaire. The result of this research was a valid studentÃƒÂ¢Ã¢Â‚Â¬Ã¢Â„Â¢s worksheets website based on guided discovery on polyhedron concept. This product has been declared valid with very good criteria, by two validators. Then, the valid product was being tested limitedly at MTsN to know studentÃƒÂ¢Ã¢Â‚Â¬Ã¢Â„Â¢s response. The respondent sample was divided into two groups of student, the superior group and the regular group. The response of product usefulness from superior group had been examined as good. Therefore, the response from regular group was very good. ÃƒÂ‚Ã‚Â Based on the results, the response of 8th grade students (class VIII-2 and VIII-5) at MTsN, overall was good.